Transformational Leadership dan Job Performance dengan Self Efficacy sebagai Variabel Mediasi pada Anggota Tentara Nasional Indonesia Angkatan Darat (TNI-AD) - Rizka Kurniawati (Indonesian Journal of Behavioral Studies, 2022)
Every individual has different characteristics and characteristics. The characteristics and characteristics of individuals can be influenced from internal and external. Institution member who lacks ability, he cannot complete his responsibilities to the fullest. For this reason, it is necessary to pay attention to the factors that can affect the performance of members, the problem of decreased performance can be detrimental to members of the organization or employees and the company. The purpose of this study is to see whether there is a relationship between perceptions of transformational leadership and self-efficacy on performance among members of the Army. In this study using a quantitative approach to simple regression analysis with a total sample of 80 members. Obtained results that have a positive and non-significant effect between perceptions of transformational leadership and performance with self-efficacy as mediating variables β = 0.166; p = 0.189) which shows that self-efficacy is not a mediating variable between transformation leadership and performance.